2012
DOI: 10.1158/1078-0432.ccr-11-2353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Non–Small Cell Lung Cancers Harboring Different Exon 19 Deletions in EGFR

Abstract: Purpose: Several deletions in exon 19 of epidermal growth factor receptor (EGFR) gene have been reported in non–small cell lung cancer (NSCLC). It is unknown if deletions occurring at different amino acid positions or of different sizes are associated with different clinical outcome to EGFR tyrosine kinase inhibitors (TKI). Experimental Design: This study enrolled NSCLC patients with deletions in EGFR exon 19. Patients who had received EGFR TKIs for advanced NSCLC were further evaluated for resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 28 publications
6
65
0
Order By: Relevance
“…17 Supporting the importance of this residue, exon 19 deletions that do not include a substitution at 747 have been found to have poorer outcomes when treated with TKI. 27 The lack of structural consistency among the exon 20 insertions may indicate a particularly varied biology among this family of mutations. Indeed, cell line studies have recently indicated that one variant of exon 20 insertions, A763_Y764insFQEA, is actually sensitive to treatment with erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…17 Supporting the importance of this residue, exon 19 deletions that do not include a substitution at 747 have been found to have poorer outcomes when treated with TKI. 27 The lack of structural consistency among the exon 20 insertions may indicate a particularly varied biology among this family of mutations. Indeed, cell line studies have recently indicated that one variant of exon 20 insertions, A763_Y764insFQEA, is actually sensitive to treatment with erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the deletions in exon 19 encompass the amino acids from codons L747-750 (LRE fragment) which activate EGFR and respond to EGFR-TKI, while the other deletions which do not involve any of the LRE fragment are reported to have a worse response (2). This may be because that the LRE deletion mutation can significantly change the conformation of a protein in this region from the initial to the "active dimer" state and can keep the state longer (3).…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the phosphorylation of this mutation variant using a phospho‐Y1092‐specific antibody and an anti‐phosphotyrosine antibody; phosphorylation was at a low level compared to WT EGFR or L858R. Although it is unclear why only del747–752 is not as highly phosphorylated at Y1092, patients with del747–752 mutation benefit from EGFR‐TKI treatment . A possible hypothesis is that this EGFR mutation may be activated by heterodimerization with HER2 or human epidermal growth factor receptor type 3 (HER3).…”
Section: Discussionmentioning
confidence: 99%